Glacial Southern Ocean deep water Nd isotopic composition dominated by benthic modification - Hallmaier, Moritz; Rückert, Eva Marcella; Chen, Yugeng; Link, Jasmin; Lizio, Riccardo; Lohmann, Gerrit; Gutjahr, Marcus; Frank, Norbert (Scientific reports, 2025)
The deep Southern Ocean (SO) circulation plays a key role in the storage and release of CO2 in Earth’s climate system. The uptake and release of CO2 strongly depend on the redistribution of well and poorly ventilated deep ocean water masses. Recently, evidence was found for possible stronger Pacific deep water overturning and subsequent intrusion into the SO during periods of reduced AMOC. Here, we present new authigenic neodymium isotope data (ɛNd) from two sites within the Atlantic sector of the SO to assess the distribution of water masses during the past 150 ka. PS 1768-8 (3299 m) and ODP 1093 (3624 m) feature unradiogenic interglacial ɛNd-signatures, which are typical for present-day Weddell Sea sourced Antarctic Bottom Water (AABW) (ɛNd ~  − 8.6). During peak glacial periods, radiogenic ɛNd-values ranging from ~  − 2.5 to − 3.5 are recorded. This may be the result of either a strong Pacific or benthic flux influence on the Nd budget in the Atlantic sector of the SO. However, an ocean circulation model indicates no stronger Pacific influence during glacials. Thus, we suggest that an increase in benthic flux influences the SO Nd budget, which is modulated by ACC strength. The more stratified and more sluggish deep water supports decreased vertical mixing and increased glacial carbon storage without the intrusion of poorly ventilated Pacific waters. The occurrence of highly radiogenic glacial bottom water or porewater signatures requires reassessment of the glacial Southern Hemisphere ɛNd-endmember for water mass sourcing reconstructions in the glacial Atlantic.
Gesehen am 28.07.2025